Being Muslim the Bosnian way identity and community in a central Bosnian village - Bringa, Tone (Princeton studies in Muslim politics, 1995)
I have been able to follow a Bosnian community over a period of six years, during which it has undergone dramatic changes and events. This is a gripping and heartfelt account of a community that has been torn apart by ethnopolitical conflict. It will attract readers of all backgrounds who want to learn more about one of the most intractable wars of the late twentieth century and the people who have been so tragically affected.